Phytochemical analysis and biological activities of Salvia candidissima subsp. candidissima mericarps - Sevda Güzel Kara; Zehra Öksüz; Şerife Selma Uras Güngör; Samet Belveren; Ahmet Kahraman (Botanica Serbica, 2023)
The sterol, amino acid, mineral, total phenolic, and total flavonoid contents, and the antioxidant, antimicrobial, and antibiofilm activities of Salvia candidissima subsp. candidissima mericarps were investigated. The mericarps were collected in the province of Bayburt, Turkey. Gas chromatography was used for sterol analysis, Prominence ultra-fast liquid chromatography for amino acid analysis, and ICPMS for mineral analysis. Folin-Ciocalteu, Al(NO3 )3 , and DPPH radical scavenging activity assays were performed on ethanol extracts of the mericarps to evaluate the total phenolic and flavonoid contents, and antioxidant potential, respectively. The ethanol and hexane extracts of the mericarps were tested for their antimicrobial activity against seven bacterial and three fungal strains using the microdilution method and for antibiofilm activity against Pseudomonas aeruginosa biofilm using the crystal violet staining method. The sterol, amino acid, and mineral contents and antibiofilm activity of the mericarps were studied for the first time. The most abundant components of the mericarps are determined as β-sitosterol (69.8%), glutamic acid (4895 mg/100 g), and potassium (11474 µg/g). The results of total phenolic and flavonoid contents and DPPH free radical scavenging activity were 3.47 µg GAE/mg extract, 0.35 µg QE/mg extract, and 79.79%, respectively. Both of the tested extracts exhibited antimicrobial activity against all the tested microorganisms, however, the efficiency of the extracts was not as strong as the reference drugs ampicillin and fluconazole. While both extracts were effective in preventing biofilm formation, the ethanol extract was found to be more effective than the hexane extract in preformed biofilm inhibition. In conclusion, S. candidissima subsp. candidissima mericarps have good nutritional potential with high amounts of amino acids, sterols (especially β-sitosterol), minerals, and phenolics and flavonoids. Additionally, our findings provide important preliminary data for the literature in terms of the antibiofilm activity of Salvia candidissima subsp. candidissima mericarps.